Studies on the dissipation pattern of Thiacloprid and Hexythiazox on apple in Kashmir - Khan, Abid S; Sheikh, Bilal; Khan, Zakir S; Bhat, Mohmad Sayeed (Journal of Postharvest Technology, 2018)
Indiscriminate use of pesticides against insect pests and diseases pose a potential threat to our living environment. . Exposure to the pesticide residues causes number of ailments in human beings. Food commodities like fruits, vegetables, cereals etc. having excessive residues, are unacceptable both in the national and international markets. It was, therefore thought pertinent to undertake the investigation on the determination of pesticides residues in apple and to study the dissipation behaviour of the two newly inducted pesticides thiacloprid (21.7SC) and hexythiazox (5.45EC). An apple orchard at Lousdanew (Shopian Kashmir India) having 15 years old Red Delicious cultivar was selected for the experiment. Each pesticide was sprayed at two concentrations, thiacloprid (21.7SC) at the concentration of 0.0096 and 0.0192 percent and hexythiazox (5.45EC) at the concentration of 0.002 and 0.004 percent, were applied by 30th August before one month of harvesting apple fruit. . Representative samples weighing about 1kg were taken and reduced to 15g by standard quartering technique for residue analysis, by using Buffered QuEChERS technique and quantified on HPLC Dionex 3000 ultimate with PDA detector. The residues of thiacloprid (21.7SC) on Red Delicious apples recorded initial deposits of 0.784 ppm and 0.901 ppm from 0.0096 and 0.0192 percent concentrations with a dissipation of 91.07 and 89.78 percent in 15 days, respectively. The dissipation was dose dependent as residues from higher concentration of 0.0192 percent persisted for 30 days while residues from lower concentration of 0.0096 percent persisted only up to 15 days. Similar behaviour was observed in case of hexythiazox (5.45EC) as the higher concentration of 0.004 percent left an average initial deposit of 0.790 ppm which recorded dissipation of 99.74 percent in Red Delicious apples and residue persisted up to 30 days (harvest time) while the lower concentration of 0.004 percent left an average initial deposit of 0.670 ppm in Red Delicious cultivar which recorded dissipation of 99.73 percent, and residues persisted up to 15 days only. Both concentrations of hexythiazox degraded faster than thiacloprid which degraded fairly slowly. The higher concentration of thiacloprid (0.0192 percent) degraded with half-life value of 6.57 days while the lower concentration of 0.0096 percent dissipated with half-live value of 4.70 days in Red Delicious varieties. Similarly, the higher concentration of hexythiazox 0.004 percent degraded with half-life value of and 6.68 days while the lower concentration of 0.002 percent dissipated with half-live values of 1.88 days in Red Delicious varieties. The residues of both pesticides at recommended concentrations could not be detected in harvest time fruits indicating 100 percent dissipation of pesticides at the harvest time. Based on the MRL value of 0.3 mg/kg for thiacloprid on Red Delicious, the waiting periods of 5.82 and 7.17 days at 0.0096 and 0.0192 percent concentrations, respectively, were worked out for the safe consumption of the fruit. Again, on the basis of 0.2 mg/kg MRL value of hexythiazox on Red Delicious, the waiting periods of 4.37 and 9.31 days at 0.002 and 0.004 percent concentrations, respectively were worked out for the safe consumption of the fruit.